Importance and knowledge in psychological assessments: a study with Psychology students - Noronha, Ana Paula Porto; Nunes, Maiana Farias Oliveira; Ambiel, Rodolfo Augusto Matteo (Paidéia (Ribeirão Preto), 2007)
This study analyzed the level of importance that psychology students give to their competence and knowledge in psychological assessments. One hundred and twelve students from the central-west region of the country, mainly women, from all periods of the course, participated in the study.The questionnaire used was based on the definition of essential competencies as indicated by the American Psychological Association,and was composed by 20 items answered separately for competence and importance. It addressed themes like knowledge about psychological constructs and how to use and interpret tests, among others. Items considered less important were "having statistical notions" and "knowing a wide range of tests". Some contradictions were found when importance and knowledge were compared, as for example in the knowledge of statistical principles. The ANOVA statistical analysis revealed few differences related to importance items between students of different years of the course, but most knowledge items showed significant differences.